2001
DOI: 10.1002/nme.327
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Schwarz preconditioners for spectral element discretizations of convection‐diffusion problems

Abstract: SUMMARYThe classical overlapping Schwarz algorithm is here extended to stabilized spectral element discretizations of convection-di usion problems. The algorithm solves iteratively the resulting non-symmetric system of linear equations by a preconditioned GMRES method. The preconditioner is built from local convection-di usion solvers on overlapping subdomains and from a coarse convection-di usion solver on a coarse mesh deÿned by the subdomain boundaries. Several numerical experiments on test problems in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…UsingF as a preconditioner allowed FGMRES to obtain convergence rates independent of the mesh size, and mildly dependent of changes in convection strength. Our results compare favorably with those reported in [1], [7], [13] and [19].…”
Section: Variable Wind Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…UsingF as a preconditioner allowed FGMRES to obtain convergence rates independent of the mesh size, and mildly dependent of changes in convection strength. Our results compare favorably with those reported in [1], [7], [13] and [19].…”
Section: Variable Wind Resultssupporting
confidence: 89%
“…We demonstrated that this solution method has a weak dependence on Peclet number, and mild dependence on mesh refinement for both h-refinement and p-refinement. Similar conclusions have been reported in [1], [13] and [19] for overlapping and non-overlapping domain decomposition strategies. The use of FDM in our method significantly reduces the computational cost of the subsidiary interior solves throughout the calculation.…”
Section: Variable Wind Resultssupporting
confidence: 87%
See 2 more Smart Citations